ConcepÃÃes, prÃticas e desafios na Mostra de EducaÃÃo Ambiental do CearÃ: o que fazem em educaÃÃo ambiental os professores de ciÃncias naturais? - Diego Adaylano Monteiro Rodrigues (2016)
ABSTRACT The general purpose of this research is to understand how the environmental dimension is translated into the conceptual and practice experiences of natural sciences teachers. These educators develop environmental education activities in Fortaleza (CE) and were awarded in the Exhibition of Environmental Education of the State Teaching Network in CearÃ (MEA). This study uses theoretical background from the âEnvironmental Educationâ (EE) and âSciences Teachingâ (ST), focusing on concepts of Critical EE, Technological-Scientific Literacy, and Science, Technology, Society and Environment (STSE). The investigation method employed in this thesis has a qualitative nature. In the first phase of this study, we surveyed three MEA organizers who are responsible for EE in Fortaleza and the State of CearÃ. Additionally, we analyzed the documents related to the event. Regarding to the faculty (second phase), five women were selected from the State Teaching Network of Fortaleza. Data was gathered using questionnaries, semi-structured interviews, and through the analysis of documented reports sent to MEA. Data evaluation was substantiated by Content Analysis. We realized that MEA is related to other federal and state public policies, specially the ones that promote a sustainability culture in schools. Regarding EE, the event does not make a speech in unison, since one of its purposes is to present conservationist, scientific, resolute and critical insights. The teachers of Natural Sciences and Geography are the most common project advisors, and they usually talk about themes related to rubbish reduction and wastefulness. The MEA is represented by teachers and organizers as a stimulating, action-sharing, reporting and learning space, which highlights the importance of the event. In the second phase of the study, which involves only the sciences teachers, we realized that these professionals often consider the environment as the place where one lives, and that this concept lacks social and political aspects. EE is limited to a pragmatic or conservationist perspective. The STâs viewpoints support the encouragement of a practical scientific literacy. The surveyed teachers tend to consider natural sciences as primary for EE practices and have more contextualized points of view regarding STSE (according to the evaluated parameters). Conceptions of EE such as parallel axis and appendix of teaching of Science are also predominant in the studied group. In other words, the teachers make a distinction between environmental and scientific contents. Among the group of participants this study, there is a noteworthy teacher who adopts a pragmatic EE conception and is engaged in the process of inserting water-related subjects in school curriculum, with the help of a group named Com-Vida. We conclude that EE proposals in synergy with TS are necessary. The proposals should 10 make curriculum alterations with interventions that query the social structures and the exagerated trust in a scientific-technological neutrality, rather than being restricted to methodological innovations which are parallel to the activities developed in the classroom. The presence of formalized groups in schools such as Com-Vida can assist this process.